2020
DOI: 10.1186/s40510-019-0301-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of apical root resorption during orthodontic treatment with clear aligners and fixed appliances: a cone beam computed tomography study

Abstract: Background: Fixed appliances have been the mainstream for orthodontic treatment, while clear aligners, such as Invisalign system, have become increasingly popular. The prevalence of apical root resorption (ARR) in patients with clear aligners is still controversial. The aim of this study was to investigate and compare the prevalence and severity of ARR in patients treated with clear aligners and fixed appliances using cone beam computed tomography (CBCT). Materials and methods: A total of 373 roots from 70 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 34 publications
1
76
1
13
Order By: Relevance
“…Both panoramic radiographs and CBCT were used in the earlier studies to assess tooth root length [ 20 , 21 , 26 , 30 ]. Currently, CBCT has been widely used in orthodontic treatment as an important tool for determining impacted tooth location [ 32 ], facial asymmetry [ 33 ], supernumerary teeth, temporomandibular joint (TMJ) pathology [ 34 ], airway construction, as well as for surgical planning [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both panoramic radiographs and CBCT were used in the earlier studies to assess tooth root length [ 20 , 21 , 26 , 30 ]. Currently, CBCT has been widely used in orthodontic treatment as an important tool for determining impacted tooth location [ 32 ], facial asymmetry [ 33 ], supernumerary teeth, temporomandibular joint (TMJ) pathology [ 34 ], airway construction, as well as for surgical planning [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported that the degree of EARR for fixed appliances is about 1.67 ± 0.64 mm for maxillary central incisors [ 40 ]. Another recent study has shown an average of 1.12 ± 1.34 mm root resorption for fixed appliance [ 20 ]. Thus, our data is in accordance with the previous study that the severity of EARR in patients using clear aligners was less than those using the fixed appliance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These types of repair could adversely affect the volume of the pulp. Multiple studies tested the effect of orthodontic tooth movements by using, for example, histological assessment using light or scanning electron microscopy and 2-dimensional radiograph [3,14,[25][26][27]. These methods, however, have a limitation that could reduce their accuracy.…”
Section: Discussionmentioning
confidence: 99%